Engineering secure software and systems : 4th International symposium, ESSoS 2012, Eindhoven, The Netherlands, February, 16-17, 2012. Proceedings - Barthe, Gilles (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 4th International Symposium on Engineering Secure Software and Systems, ESSoS 2012, held in Eindhoven, The Netherlands, in February 2012. The 7 revised full papers presented together with 7 idea papers were carefully reviewed and selected from 53 submissions. The full papers present new research results in the field of engineering secure software and systems, whereas the idea papers give crisp expositions of interesting, novel ideas in the early stages of development.